Pengetahuan Persepsi Ibu Dan Dukungan Suami Terhadap Frekuensi Pelaksanaan ANC Pada Ibu Primigrafida Di BPS Desa Sawo Kutorejo Mojokerto - Nina Primasari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2010)
Antenatal care is observation to pregnant mother by preparing her the best physically or mentally in pregnancy, bearing and child bed in good condition and normal. This interconnected by mortally mother in Indonesia is very high. In year 2002, it gets 343/100.000 bith of life. The mortally mother is one indications of mother healthy. Based on description above, the researcher supposes to know level preseption of knowledge mother and housband’s support to frequency of ANC action. This research is descriptive, technique taking the sample uses non probability smpling by puposive sampling. This research is done on 2005 september 13th – 14th, by amopunt 42 responders. Data are collected by using questioner and getting obeservation. After data gotten, they are crossed tabulation and anaylized by drawing them that gotten in narrative and percentage. The result of level distribution knowledge in action ANC 80,96% well is suitable with standard in acton 41,76 isn’t suitable. Perception to frequency ANC 88,10% is good perception. Husband’s support to frequency ANC 88,10% is good husband’s support.